Considerations regarding the use of rigid sails on modern powered ships. Issue 1 (1st January 2018) - Atkinson, Gregory; Nguyen, Hung; Binns, Jonathan
Abstract: The global shipping fleet is vital to world trade with billions of tonnes of cargo being transported annually by merchant vessels. This activity however results in large volumes of carbon emissions and airborne particulate matter being released into the atmosphere due to the burning of fossil fuels for propulsion and on-board power. Recently, there has been an increasing focus on the need to reduce fossil fuel consumption and airborne emissions across the shipping sector. To facilitate this, a range of technologies have been developed or are currently in the development phase. Rigid sails are one of these technologies, yet despite these being installed on a number of ships in the 1980s they have to date been unable to gain widespread acceptance. This paper will briefly discuss the history of sails on ships and then review a broad range of issues regarding their use encompassing previous research studies, journal articles and operational experiences.